Consumer salience and quality provision in (un)regulated public service markets - Yiquan Gu; Alexander Rasch; Tobias Wenzel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper examines the publication of quality indicators in service markets with public finance systems, such as education and healthcare markets. We provide a spatial model of product differentiation in which the reporting of such indicators increases consumers' decision weight on quality relative to other attributes (such as prices and horizontal match) and study the effects in two market environments: markets with regulated prices and markets with unregulated prices. We find that the publication of quality indicators increases quality investments by service providers, but also leads to higher prices and less product variety. Consumer and total welfare may decrease with such policies, in particular when consumers are heavily subsidised.
Keywords: L15; L51; I10; I20; 330; Service markets; Quality reporting; Variety; Entry; Regulation; Public finance